2022
DOI: 10.3389/fendo.2022.865930
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Adipose Tissue Accumulation Is an Independent Risk Factor of Urinary Stone in Young People

Abstract: BackgroundUrinary stones usually start at a young age and tend to recur. Therefore, preventing stone occurrence and recurrence in young people is crucial. We aimed to investigate the association between subcutaneous adipose tissue, visceral adipose tissue, and stone episodes in young people.MethodsWe retrospectively studied patients aged below 40 years with kidney or ureteral stones. Data on demographic and metabolic characteristics, urolithiasis history, subcutaneous fat area (SFA), and visceral fat area (VFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, one study reported con icting results, suggesting a stronger association between subcutaneous fat and nephrolithiasis risk 23 . Key differences in study design, including sample size, age group, and study type, may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported con icting results, suggesting a stronger association between subcutaneous fat and nephrolithiasis risk 23 . Key differences in study design, including sample size, age group, and study type, may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in food habits and the increased incidence of obesity are the main causes of the rising prevalence of ureteral calculi [1,2]. Clinically, Medical Expulsive Therapy (MET) is beneficial due to its minimal trauma and complications.…”
Section: Introductionmentioning
confidence: 99%